Usefulness of the plasma branched-chain amino acid/aromatic amino acid ratio for predicting future cardiac events in patients with heart failure. Issue 6 (June 2020) - Hiraiwa, Hiroaki; Okumura, Takahiro; Kondo, Toru; Kato, Toshiaki; Kazama, Shingo; Ishihara, Toshikazu; Iwata, Etsuo; Shimojo, Masafumi; Kondo, Sayano; Aoki, Soichiro; Kanzaki, Yasunori; Tanimura, Daisuke; et al.
Highlights: Amino acids metabolic imbalance occurs in patients with heart failure. The plasma branched-chain amino acid/aromatic amino acid ratio (Fischer's ratio; FR) can predict cardiac events in heart failure patients. FR reflects nutritional status that cannot be detected by liver function tests and geriatric nutritional risk index. Abstract: Background: Heart failure (HF) is a hypercatabolic state that promotes branched-chain amino acid (BCAA) catabolic activity in the heart and skeletal muscle and reduces protein synthesis in the liver. Consequently, plasma free aromatic amino acids (AAAs) are increased. We investigated the prognostic value of the BCAA/AAA ratio (Fischer's ratio, FR) in patients with HF. Methods: We enrolled 157 consecutive patients hospitalized for worsening HF (81 men, 76 women; mean ± SD age 75 ± 14 years). Plasma BCAA levels (i.e. total leucine, isoleucine, valine) and AAA levels (i.e. total tyrosine, phenylalanine) were measured at a time when the patients were stabilized (at discharge). FR was calculated as the combined plasma BCAA levels divided by the AAA level. Cardiac events were defined as a composite of cardiac death and hospitalization for worsening HF. Results: The patients were divided into two groups based on the median FR (high-FR group: FR ≥ 3.1, n = 78; low-FR group: FR < 3.1, n = 79). Compared with the high-FR group, low-FR patients were older, had more prior hospitalizations for HF, lower albumin and cholinesterase levels, and lower geriatric nutritional risk index (GNRI). Altogether, 46 cardiac events occurred during the follow-up period (221 ± 135 days), including 14 cardiac deaths and 32 hospitalizations for worsening HF. In a Kaplan–Meier survival analysis, the low-FR group had more cardiac events than the high-FR group (log-rank, p  < 0.001). The best cut-off value of FR was determined as 2.9 in the receiver operating characteristic curve for cardiac events. A multivariate Cox proportional hazards regression analysis showed that being in the low-FR group was an independent determinant of cardiac events from parameters of liver function tests and GNRI. Conclusions: FR might be useful for predicting future cardiac events in patients with HF, reflecting nutritional status which cannot be assessed by liver function tests and GNRI.